The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijns6030051
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Expanded Newborn Screening in Norway Supported by Post-Analytical Bioinformatics Tools and Rapid Second-Tier DNA Analyses

Abstract: In 2012, the Norwegian newborn screening program (NBS) was expanded (eNBS) from screening for two diseases to that for 23 diseases (20 inborn errors of metabolism, IEMs) and again in 2018, to include a total of 25 conditions (21 IEMs). Between 1 March 2012 and 29 February 2020, 461,369 newborns were screened for 20 IEMs in addition to phenylketonuria (PKU). Excluding PKU, there were 75 true-positive (TP) (1:6151) and 107 (1:4311) false-positive IEM cases. Twenty-one percent of the TP cases were symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 58 publications
4
40
0
2
Order By: Relevance
“…Tandem mass spectrometry (MS/MS) technology also has become a routine method in many countries. Croatia plans to introduce next-generation sequencing (NGS) technology as a second-tier for some conditions, which is already done in Norway to detect CF mutations and to detect mutations underlying many disorders in the programme [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tandem mass spectrometry (MS/MS) technology also has become a routine method in many countries. Croatia plans to introduce next-generation sequencing (NGS) technology as a second-tier for some conditions, which is already done in Norway to detect CF mutations and to detect mutations underlying many disorders in the programme [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…We considered the use of next-generation sequencing technology, reduced costs and greater access to MS/MS and the use of big data technology (e.g., the application of R4S/CLIR to evaluate screening results) as important changes [ 34 , 35 , 36 , 37 ]. Finland, Iceland, Norway and Sweden use CLIR for evaluation of individual screening results [ 26 , 38 ]. The Czech Republic uses the CLIR website to evaluate cut-off levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most laboratories use commercial kits that screen for a predefined mutation panel covering the more prevalent pathogenic variants. In recent years, many pilot projects have introduced DNA analysis into NBS before the family is alerted [ 85 , 86 , 87 , 88 ]. A retrospective study conducted in Pennsylvania evaluated the feasibility of a DNA-based 2-TT, covering the most common GALT mutations (seven mutations and two variants), to improve the specificity of NBS for Galactosemia.…”
Section: Molecular Testing As a 2-ttmentioning
confidence: 99%
“…It was found that sensitivity and specificity of WES was in fact lower than the MS/MS method but there was possible utility of WES as a second tier [ 10 ]. In Norway, a study looked at the utility of Next Generation Sequencing (NGS) as a second tier to supplement NBS and showed benefit [ 11 ]. Pilot programs in the United States at several different sites used various genomic sequencing technologies to screen for conditions beyond the traditional NBS and looked at the utility both in populations of sick newborns and in those that are healthy [ 12 ].…”
Section: Ethical Considerations Of Nbs and Incorporation Of Genomimentioning
confidence: 99%